Audit of fidelity of implementation of the older prisoner health and social care assessment and plan (OHSCAP). Issue 1 (2nd January 2022) - Forsyth, Katrina; Swinson, Nicola; Archer-Power, Laura; Senior, Jane; Shaw, Daisy; Shaw, Jenny
ABSTRACT: Numbers of older prisoners have been increasing in recent years and there is no national strategy addressing their care. Older prisoners have more physical health needs, complex social care needs and high rates of mental disorder compared with younger prisoners. These needs are often not identified or addressed. We developed the Older prisoner Health and Social Care Assessment and Plan (OHSCAP), a structured approach for identifying and managing the health and social care needs of older prisoners. It consists of an assessment, care plan and review of needs. The current study aims to establish the fidelity of implementation of the OHSCAP as part of a larger RCT. Compliance, context and competence fidelity were audited to assess compliance with training and the manual, adequacy of completion and identification of needs and quality of care planning. Results showed that the OHSCAP was not implemented as intended with needs identified not being consistently translated into care plan actions, little evidence to suggest that prisoner involvement in the care planning process and difficulties in collaborative working. Implications with respect to effectively embedding complex interventions within prisons, along with wider policy-related issues affecting the entire prison estate are discussed.